PENERAPAN KANCING GEMERINCING DALAM MENINGKATKAN TEAMWORK SKILL PADA MAHASISWA PGSD FKIP UMSU - AMELIA, CHAIRUNNISA; PRATIWI, INDAH (Jurnal Ilmiah Aquinas, 2020)
This study aims to determine the ability of students to work together in groups or teamwork skills, and to determine student responses in learning in social studies courses using the jingle learning model which is expected from the application of jingle learning model can be seen an increase in learning outcomes student in class. The method used in data collection is documentation, observation and test giving to students. In this research, it can be seen that there is an increase in the ability to work together with students in groups, which in the future will function for students to continue solidarity within groups in other subjects. In learning that uses a different learning model results in the ability of students when understanding a material compared to not using a classical learning or learning model. This can be seen from the average student learning outcomes before using the learning model and by not implementing teamwork skills only 65.2 and learning outcomes using the jingle learning model by applying teamwork skills 93.5. The results obtained can be seen the use of learning models can improve team work skills in PGSD students